Developing Blended Learning Teaching Model through Online Social Media Platform as Learning’s Support - Agusti Mardikaningsih; Praharisti Kurniasari (Madrosatuna: Journal of Islamic Elementary School, 2021)
Technology develops rapidly and it affects the technology development at physical, health, and recreation education study program of IKIP Budi Utomo as this year they uses combination learning approach. Students can study anywhere, anytime, and with whomever. To support the current availability of the facilities, the lecturers are required to develop various learning plan models which are easy and comprehensive; one of them is Blended Learning Model. The objective of this research is to develop blended learning model teaching scenario plan and develop blended learning application using social media as the media to ease the teaching and learning process. Online social media were chosen as the basic platform to distribute learning materials and communicate online because of the determinations of usage affordability, effectiveness, and familiarity. The development of blended learning scenario and application used ADDIE Model because it was a general/common learning system model and one of product development models. There is evaluation in each step of ADDIE model. Evaluation is done through validation process and the collected data were analyzed using percentage technique, they are: per item data tabulation and whole data tabulation. Based on the research result, it could be concluded that the percentage of Blended Learning Teaching Scenario developed was considered as appropriate and able to improve the students’ comprehension significantly.